2020
DOI: 10.3390/ijms21031115
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immunity: A Common Denominator between Neurodegenerative and Neuropsychiatric Diseases

Abstract: The intricate relationships between innate immunity and brain diseases raise increased interest across the wide spectrum of neurodegenerative and neuropsychiatric disorders. Barriers, such as the blood–brain barrier, and innate immunity cells such as microglia, astrocytes, macrophages, and mast cells are involved in triggering disease events in these groups, through the action of many different cytokines. Chronic inflammation can lead to dysfunctions in large-scale brain networks. Neurodegenerative diseases, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 288 publications
(304 reference statements)
1
50
0
Order By: Relevance
“…Astrocytes have a basic physiological function in forming borders to restrict access of leukocyte into brain parenchyma [31]. They also provide energy sources for neurons, modulate synaptic activity, and regulate extracellular glutamate levels [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Astrocytes have a basic physiological function in forming borders to restrict access of leukocyte into brain parenchyma [31]. They also provide energy sources for neurons, modulate synaptic activity, and regulate extracellular glutamate levels [38].…”
Section: Discussionmentioning
confidence: 99%
“…It is mainly caused by activated glial cells and manifests as the secretion of inflammatory cytokines. Astrocytes are the most abundant glial cells in the brain, and they play a pivotal role in regulating inflammatory response in a variety of neurodegenerative diseases [31]. In order to investigate whether they are related to PPD, we detect the GFAP, a marker of astrocytes, by immunofluorescence.…”
Section: Nlrp3 Inflammasome Was Activated In Hippocampus Of Ppd Modelmentioning
confidence: 99%
“…Complex intra-and extracellular interactions of the innate-and adaptive-immune systems and inflammatory mediators including microglial activation, pro-inflammatory cytokines, and chemokines coordinate critical aspects of acute and chronic inflammation. These in turn orchestrate a series of common interactive effector mechanisms of tissue inflammation that contribute interactively to angiogenesis, amyloidogenesis, remodeling of the extracellular matrix, tissue injury moderated in part by reactive oxidative species (ROS), and the recruitment of blood leukocytes that (i) in many tissues characterize the initiation of inflammation, and (ii) influence critical temporal aspects of disease initiation and progression (45)(46)(47)(48)(49)(50)(51).…”
Section: Mirna-146a and Inflammatory Neurodegenerationmentioning
confidence: 99%
“…AD like PrD possesses a progressive neuropathology, in part based on the aggregation of abnormal lipoprotein assemblies that result in their recognition by microglia, microglial activation, and the induction of pro-inflammatory signaling cascades that support irreversible neurodegenerative pathways. It appears that the neuroinflammation associated with AD and PrD, and other human neurodegenerative maladies may represent classical examples of an important pathological process involving cyclic, self-reinforcing, and relentless propagation of neuroglial cell activation, release of pro-inflammatory cytokines and related pathogenic factors and neuronal damage, atrophy, dysfunction, and degeneration (47)(48)(49)(50)(51)(52)(53). It has recently been suggested that the provision of highly pathogenic prokaryotic signals from the GI tract microbiome involving secreted pro-inflammatory glycolipids such as Bacteroides fragilis LPS and enterotoxins such as the hydrolase fragilysin (EC 3.4.24.74) often found in abundance in the systemic circulation and brain parenchyma of AD and/or PrD patients may well contribute to the initiation and/or propagation of these progressive and irreversible agerelated neurodegenerative disease processes (20,29,(44)(45)(46).…”
Section: Mirna-146a and Inflammatory Neurodegenerationmentioning
confidence: 99%
“…The toxic accumulation of proteins and metabolites is also partially responsible for the neuroinflammation process that is common to almost all neurodegenerative diseases. Today, innate immunity, with the particular relevance of glial cells, is considered to have a central role in brain homeostasis neurodegenerative events [317]. Indeed, sequencing and GWAS studies contributed to highlight the role of immunity and microglia as important contributors to the pathological events occurring in neurodegenerative diseases.…”
Section: Neurodegeneration Metabolic Alteration and Admentioning
confidence: 99%